2013
DOI: 10.4172/2167-0846.1000119
|View full text |Cite
|
Sign up to set email alerts
|

Impact of A118G Polymorphism on the Mu Opioid Receptor Function in Pain

Abstract: Mu Opioid Receptor (MOR) activation by exogenous or endogenous agonists causes reduction of pain threshold after a noxious stimulus, relieving pain sensation. MOR is encoded by OPRM1 gene and its messenger RNA suffers extensible modifications by alternative splicing and single nucleotide polymorphisms (SNPs). A118G (N40D) is the most frequent encoding MOR SNP in humans. In this review we discuss the impact of this polymorphism at molecular, cellular and clinical levels. Since some SNPs are unequally distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(93 reference statements)
0
2
0
1
Order By: Relevance
“…The SNP rs1799971 (A > G) results in an amino acid change from asparagine to aspartic acid in the OPRM1 (binding site for fentanyl) and finally leading to its decreased expression. [15][16][17][18][19] This may lead to lesser postoperative fentanyl requirement in patients carrying this SNP. Sia et al 20 reported that 24-hour morphine requirement in postcaesarean patients was lower in the patients with "A/A" genotype (OPRM1) when compared to "A/G" and "G/G" genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The SNP rs1799971 (A > G) results in an amino acid change from asparagine to aspartic acid in the OPRM1 (binding site for fentanyl) and finally leading to its decreased expression. [15][16][17][18][19] This may lead to lesser postoperative fentanyl requirement in patients carrying this SNP. Sia et al 20 reported that 24-hour morphine requirement in postcaesarean patients was lower in the patients with "A/A" genotype (OPRM1) when compared to "A/G" and "G/G" genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…10,26,37 The SNP rs1799971 is a missense variation (A.G) in the OPRM1 gene, which encodes the mu opioid receptor (binding site for fentanyl). 2,22,42 The SNP rs1801253 is also a missense variation (C.G) in the ADRB1 gene, which encodes the Beta-1 adrenergic receptor (binding site for neurotransmitters-norepinephrine and epinephrine released in CNS pain circuits). 24 The SNP rs2242480 in the CYP3A4 gene which encodes the enzyme responsible for .99% of metabolism of fentanyl has been found to be associated with increased opioid requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Las consecuencias del cambio de N por D en la posición extracelular 40 incluyen que el subtipo MOR-D (que contiene D en la posición 40) posea un sitio menos de glicosilación que el MOR-N (que contiene N en la posición 40) ya que N40 constituye, junto a otros cuatro residuos N, sitios de glicosilación (Mestek et al, 1995;Huang et al, 2012). Adicionalmente, en diferentes estudios in vitro se han evaluado otros efectos de N40D sobre la función del receptor, obteniéndose resultados conflictivos hasta el momento (Lopez Soto et al, 2013). En ensayos de expresión, el receptor mutado MOR-D mostró mayor afinidad de unión a la β-endorfina, que el receptor MOR-N (Bond et al, 1998).…”
Section: El Receptor Opioide µunclassified